2020
DOI: 10.1093/jac/dkaa319
|View full text |Cite
|
Sign up to set email alerts
|

Simplification to dual therapy containing lamivudine and raltegravir or dolutegravir in HIV-infected patients on virologically suppressive antiretroviral therapy

Abstract: Background Antiretroviral dual regimens including lamivudine and one boosted PI or dolutegravir are warranted in order to optimize combination ART (cART), prevent long-term toxicity and reduce the cost of treatments. Objectives We hypothesized that a maintenance dual regimen of lamivudine plus raltegravir would be effective and as well tolerated as the dual maintenance combination of lamivudine plus dolutegravir. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…In the other two studies, one population was 29% White, 45% Black, and 27% Hispanic [ 42 ] and the other population was 52% White, 35% Black, and 13% Asian [ 43 ]. Median ages ranged from 34.0 to 60.5 years among the 17 studies that reported median age [ 29 – 37 , 39 , 41 , 42 , 44 , 45 , 47 , 48 ]. Among studies clearly reporting treatment history, 4474 individuals switched from another regimen, and 73 were treatment naive (effectiveness was reported in 3489 and 69 PWH, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the other two studies, one population was 29% White, 45% Black, and 27% Hispanic [ 42 ] and the other population was 52% White, 35% Black, and 13% Asian [ 43 ]. Median ages ranged from 34.0 to 60.5 years among the 17 studies that reported median age [ 29 – 37 , 39 , 41 , 42 , 44 , 45 , 47 , 48 ]. Among studies clearly reporting treatment history, 4474 individuals switched from another regimen, and 73 were treatment naive (effectiveness was reported in 3489 and 69 PWH, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Those who switched from another regimen had extensive ART experience ranging from 1.3 to 17.9 years in studies that reported prior ART duration [ 29 , 30 , 32 – 36 , 38 , 41 , 42 , 44 , 46 – 49 ]. This analysis includes 1251 individuals who switched to dolutegravir plus lamivudine with no prior virologic failure and no known resistance where reported across eight studies [ 29 , 34 , 43 , 47 , 50 – 53 ]. Previous virologic failure was reported for 603 PWH in 9 studies [ 29 , 30 , 34 , 35 , 41 , 43 , 45 , 46 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few events of sleep disturbance and no events of weight gain were seen, though such reports have been widely observed previously. 12,[30][31][32][33][34] No clinically significant abnormalities in vital signs, laboratory assessments and physical examination from baseline were reported during the study period. This is consistent with a DTG study conducted previously in the Indian population.…”
Section: Discussionmentioning
confidence: 99%